Tatiana Aguilar-Álvarez Bay, La verdad poética en José Ángel Valente (1955-1966). El Colegio de México, México, 2011. - Peinado Elliot, Carlos (Nueva Revista de Filología Hispánica (NRFH), 2013)
Se reseña el libro: La verdad poética en José Ángel Valente (1955-1966).